PSYCHOLOGICAL ADAPTATION OF MANAGERS TO CULTURAL HYBRIDITY IN THE PROCESS OF TRANSNATIONAL INTERACTIONS (Economic journal of Lesya Ukrainka Volyn National University, 2025)
Introduction. In today’s globalized world, managers increasingly operate within transnational teams, where diverse cultures, languages, and managerial traditions intersect. This format of work requires not only professional competence but also the ability to adapt to cultural hybridity. The psychological adaptation of a manager is a key factor for effective intercultural interaction, encompassing cultural intelligence, cognitive flexibility, stress resilience, and communication skills.Methods. The study employed a mixed-methods approach combining quantitative (surveys, correlation analysis) and qualitative methods (semi-structured interviews). Standardized scales were used to assess intercultural adaptability, stress resilience, and subjective well-being (including the Kirkman-Rosen scales and an adapted version of Pak’s Cultural Adaptability Scale). The research was based on an interdisciplinary transnational approach and considered the context of cultural hybridity, cognitive flexibility, emotional regulation, and interpersonal communication.Results. The most effective strategies for reducing intercultural stress were found to be regular intercultural training (positively evaluated by 80% of respondents), peer support, and informal mentoring. High levels of cultural intelligence and cognitive flexibility were shown to correlate with lower anxiety, better adaptation, and greater leadership effectiveness in multicultural environments. Empirical evidence confirmed that managers with more than one year of international experience demonstrated lower stress levels and higher performance in solving intercultural challenges. Based on the analysis, a generalized model of managers’ adaptive components in culturally hybrid environments was proposed, including cultural intelligence, communicative competence, cognitive flexibility, emotional regulation, and adaptive leadership.Conclusions. The findings confirm that key factors of a manager’s psychological adaptation to cultural hybridity in transnational interactions include a high level of cultural intelligence, well-developed interpersonal communication skills, cognitive flexibility, and adaptive leadership capacity. The study also highlights the importance of targeted programs for the development of intercultural competencies, stress management training, and the cultivation of communicative flexibility.
Keywords: cultural hybridity, transnational interaction, cross-cultural management, intercultural intelligence, psychological adaptation, communicative competence, cognitive flexibility, stress resilience.